Effects of resveratrol on oxidant and antioxidant systems in model of rat metabolic syndrome - Ilhan, Nevin; Gungor, Hilal; Ilhan, Ayse Sebnem (Walter de Gruyter Gmbh, 2014)
Objective: In recent years, metabolic syndrome, which is a serious health problem, enhancing the effect of oxidative stress and lipid peroxidation, which is a natural antioxidant resveratrol, a polyphenol structure, the use of this area has brought. The present study aimed to evaluate the influence of resveratrol (RSV) treatment on heart, kidney and hepatic tissue malondialdehyde (MDA), nitric oxide (NO), superoxide dismutase (SOD) and catalase (CAT) levels in high fructose feeding rats which form an experimental metabolic syndrome model and compared to pre-treatment of metabolic syndrome group and the control group values. Methods: Wistar/albino rats (n=15) were used in the present study. Rats were divided equally into 3 groups as control, created group of metabolic syndrome and metabolic syndrome plus resveratrol treatment. At the end of the experimental period, tissue MDA, NO, SOD and CAT levels were studied manual spectrophotometric methods after homogenization of tissues. Results: The result of the study, a significant increase in heart and liver tissue MDA levels, and heart, kidney, liver tissue NO levels were observed in the metabolic syndrome group compared to the controls (p<0.05), following treatment with resveratrol significantly decreases were observed to be close to the control values. Kidney and liver tissue catalase activity statistically significant decrease in metabolic syndrome group compared to the controls, (p=0.019 and p=0.021, respectively), kidney and liver tissue catalase activity similar to control values after treatment with resveratrol, a significant increase was observed (p=0.011 and p=0.58), but changes in the activity of SOD has not been as significant as catalase (p>0.05). However, hepatic SOD activity of resveratrol treatment group compared with the control group, a significant increase was recorded in the treated group (p=0.011). Conclusion: These results suggest probably antioxidant effects of resveratrol to reduce oxidative stress in the liver and kidney tissue which is an important role in metabolism. Against tissue damage generated by exogenous fructose, resveratrol is effective in preventing tissue damage with a direct or indirect effect shows.
Sıçan metabolik sendrom modelinde resveratrol’ün oksidan ve antioksidan sistemler üzerine etkileri
Keywords: Metabolic syndrome; tissue MDA; NO; SOD; catalase; resveratrol